Impact Study: MK-0646 (Dalotuzumab), Insulin Growth Factor 1 Receptor Antibody Combined with Pemetrexed and Cisplatin in Stage IV Metastatic Non-squamous Lung Cancer - Huang, Chao H.; Williamson, Stephen K.; Neupane, Prakash; Taylor, Sarah A.; Allen, Ace; Smart, Nora J.; Uypeckcuat, Adelina M.; Spencer, Sarah; Wick, Jo; Smith, Holly; Van Veldhuizen, Peter J.; Kelly, Karen (Frontiers in Oncology, 2016)
Background: Insulin-like growth factor 1 receptor (IGF-1R) regulates cell growth, proliferation and apoptosis. Adenocarcinoma and never-smokers have a higher expression of IGF-1R, which is associated with worse overall survival. Dalotuzumab-MK0646 (D) is a humanized monoclonal antibody that targets IGF-1R. Pemetrexed (P) has higher activity in non-squamous lung cancer (NSQL). We initiated a randomized phase II trial to test the combination of P and Cisplatin (C) +/- D in NSQL. Methods: Eligibility criteria: untreated NSQL stage IIIB or IV, ECOG 0 or 1, measurable disease, adequate renal, hepatic and hematologic function, and no other intercurrent illness. P at 500mg/m2 and C at 75mg/m2 IV were given every 3 weeks. D was given at 10mg/kg IV weekly on days 1, 8 and 15 of every 3-week cycle in the experimental group. The patients had a radiographic assessment after every 2 cycles and were treated for a maximum of 6 cycles if there was a response or stable disease. The primary objective of the study was to compare the clinical response rates of PC vs PC+D. Results: From 1/2009 to 2/2011, the study accrued 26 subjects: 16 male and 10 female, with a median age of 59; 14 were treated with PC and 12 were treated with PC+D. We observed 2 partial responses (PR), 7 stable disease (SD), 3 progressive disease (PD), and 2 were not evaluable (NE) in the PC arm. In comparison, for the PC+D arm there were: 3 PR, 4 SD, 4 PD and 1 NE. The hematologic toxicity was similar in both groups. There higher incidence of hyperglycemia the experimental group; 4 cases with grade 3 and 1 case with grade 4. Conclusion: PC+D had a similar response rate compared to PC, with a higher rate of hyperglycemia. Identification of responders using predictive markers would be key to continuing the study of D in NSQL.